Company welfare and social work ethics: a space for social work? A discussion based on cases from Norway and Tanzania. (Journal of Comparative Social Work, 2010)
This article deals with company welfare and social work ethics. If social work is concerned with welfare and distributional issues, we would assume company welfare to be an issue of great relevance to social workers, so why do we not come across any social workers in our fieldwork? This calls for the simple question “where do social workers work?” or rather “how come social workers do not work in private companies?” We explore into the combination of social work and private companies with special reference to social work ethics to discuss private companies as a job arena for social workers. We argue that in a sector aiming at profit, social workers may trigger employees enthusiasm, but employer scepticism. However, by avoiding a less stereotyped notion of private companies, company welfare and social work we claim that certain social work ethical principles would be of joint interest to the involved, but more so in certain contexts than in others.The article consists of six sections. After the introduction, we take a closer look at company welfare followed by a section on social work where we focus on ethical principles and work arenas for social workers. In section four we present our data from some private companies in Norway and Tanzania as a point of departure to our discussion in section five on private companies as a potential job arena for social workers. The complexity of company welfare does not call for simple answers. In the conclusions, section six, we therefore argue that the ethical principles of social work make it an interesting and relevant competence in managing company welfare, though not unproblematic in the homeland of profit. However, contextual complexity invites contextual responses.